Derivative Transactions in Stock Exchanges: Between Gharar and Speculation - Sutisno; Indra Permana; Sumarta (Penerbit Hellow Pustaka, 2025)
This study aims to analyze derivative transactions in the stock exchange from the perspective of Islamic law, focusing on the concepts of gharar (uncertainty) and speculation. Employing a comprehensive literature review design, the research examines both classical and contemporary Islamic sources, as well as relevant capital market regulations. The findings reveal that purely speculative derivatives (such as futures and options without physical delivery) contain excessive gharar and are therefore problematic under Sharia principles. In contrast, derivatives designed for risk management (hedging), such as Salam Futures, Istisna’ Futures, or Ijarah-based Options, show potential compliance with Sharia when structured with clear limitations and subject to strict supervision. The implications highlight the need for a more comprehensive regulatory framework for Sharia-compliant derivatives, the development of products based on Islamic contracts, and the enhancement of Sharia financial literacy in Indonesia. The originality of this research lies in its in-depth integration of gharar and speculation analysis in the context of derivatives, offering practical guidance for the development of modern Sharia-compliant financial instruments.